2014
DOI: 10.1371/journal.pone.0096294
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Mortality in South-West Ethiopia: Estimates and Socio-Economic Inequality

Abstract: IntroductionEthiopia has achieved the fourth Millennium Development Goal by reducing under 5 mortality. Nevertheless, there are challenges in reducing maternal and neonatal mortality. The aim of this study was to estimate maternal and neonatal mortality and the socio-economic inequalities of these mortalities in rural south-west Ethiopia.MethodsWe visited and enumerated all households but collected data from those that reported pregnancy and birth outcomes in the last five years in 15 of the 30 rural kebeles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
77
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 34 publications
19
77
2
Order By: Relevance
“…Analysis of the 1997 community and family survey data in Southern Ethiopia revealed that the risk of IM is significantly associated with short birth intervals of less than 18 months compared with an interval of 24-35 months [16]. In other records mortality among neonates [18,25,26] and infants [27] with a preceding birth interval of less than 24 months was found to be 2 times higher than those with a preceding birth interval of greater than 24 months. In epidemiological assessment of determinants of U5M in Jimma town, highest rate of death was observed in groups with short birth interval [22].…”
Section: Preceding Birthmentioning
confidence: 94%
See 2 more Smart Citations
“…Analysis of the 1997 community and family survey data in Southern Ethiopia revealed that the risk of IM is significantly associated with short birth intervals of less than 18 months compared with an interval of 24-35 months [16]. In other records mortality among neonates [18,25,26] and infants [27] with a preceding birth interval of less than 24 months was found to be 2 times higher than those with a preceding birth interval of greater than 24 months. In epidemiological assessment of determinants of U5M in Jimma town, highest rate of death was observed in groups with short birth interval [22].…”
Section: Preceding Birthmentioning
confidence: 94%
“…One of the pathways by which mothers' education affects child survival is through improved child care [17]. Records revealed that neonatal mortality [18] and U5M [19] were associated with parental illiteracy; particularly maternal education has a strong relation with CM [20]. Children born to mothers with secondary education had a significantly reduced IM [16,21].…”
Section: Determinants Of Childhood Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…However study from maternity hospital of Nigeria shows 61.9% of maternal deaths occurred in post-partum period which is lower than finding from this research (74.8%). This difference might be because of sample size difference, which is only 84 maternal deaths in two year study period were included but this research includes 120 deaths in 5 year period [11,14]. Higher number of maternal death in post-partum period implies that the management following delivery and during delivery might be poor.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 49 maternal deaths, 6 (12%) occurred during pregnancy, 18 (37%) during labour, and 25 (51%) after birth within six weeks [11].…”
Section: Introductionmentioning
confidence: 99%